Dysfunctional BCAA degradation triggers neuronal damage through disrupted AMPK-mitochondrial axis due to enhanced PP2Ac interaction. - Wu, S.C.; Chen, Y.J.; Su, S.H.; Fang, P.H.; Liu, R.W.; Tsai, H.Y.; Chang, Y.J.; Li, H.H.; Li, J.C.; Chen, C.H. (Communications biology, 2025)
Metabolic and neurological disorders commonly display dysfunctional branched-chain amino acid (BCAA) metabolism, though it is poorly understood how this leads to neurological damage. We investigated this by generating Drosophila mutants lacking BCAA-catabolic activity, resulting in elevated BCAA levels and neurological dysfunction, mimicking disease-relevant symptoms. Our findings reveal a reduction in neuronal AMP-activated protein kinase (AMPK) activity, which disrupts autophagy in mutant brain tissues, linking BCAA imbalance to brain dysfunction. Mechanistically, we show that excess BCAA-induced mitochondrial reactive oxygen species (ROS) triggered the binding of protein phosphatase 2 A catalytic subunit (PP2Ac) to AMPK, suppressing AMPK activity. This initiated a dysregulated feedback loop of AMPK-mitochondrial interactions, exacerbating mitochondrial dysfunction and oxidative neuronal damage. Our study identifies BCAA imbalance as a critical driver of neuronal damage through AMPK suppression and autophagy dysfunction, offering insights into metabolic-neuronal interactions in neurological diseases and potential therapeutic targets for BCAA-related neurological conditions.